Two decades of research on ELT textbook content: A bibliometric and content analysis - Xu, Jinfen; Ye, Fan (Studies in Second Language Learning and Teaching, 2025)
Using high-quality articles obtained from the Web of Science Core Collection, this paper seeks to offer an overview of research on ELT textbook content spanning from 2003 to 2022. We first identify publication trends, prolific journals, highly cited papers, and influential references. Then, we code the collected data across four dimensions: research topics, analytical tools, textbook types, and textbook levels. Key findings reveal that there is growing academic interest in this field, with vocabulary and gender ideology as prominent themes, alongside emerging topics like task, linguistic complexity, and environmental values; and we find that corpus-based and (critical) content analyses are widely used methods. Furthermore, the distribution of research efforts appears uneven across primary school, secondary school, and university levels, as well as in the study of general English textbooks and English textbooks for specific purposes. This paper will be valuable for stakeholders involved in ELT textbook development, particularly those new to the field and seeking guidance on current research trends, methodological approaches, and emerging themes in textbook content analysis.